Gamma delta T cells in cancer therapy: from tumor recognition to novel treatments - Luo, Xinyu; Lv, Yufan; Yang, Jinsai; Long, Rou; Qiu, Jieya; Deng, Yuqi; Tang, Guiyang; Zhang, Chaohui; Li, Jiale; Zuo, Jianhong (Frontiers in Medicine, 2024)
Traditional immunotherapies mainly focus on αβ T cell-based strategies, which depend on MHC-mediated antigen recognition. However, this approach poses significant challenges in treating recurrent tumors, as immune escape mechanisms are widespread. γδ T cells, with their ability for MHC-independent antigen presentation, offer a promising alternative that could potentially overcome limitations observed in traditional immunotherapies. These cells play a role in tumor immune surveillance through a unique mechanism of antigen recognition and synergistic interactions with other immune effector cells. In this review, we will discuss the biological properties of the Vδ1 and Vδ2 T subsets of γδ T cells, their immunomodulatory role within the tumor microenvironment, and the most recent clinical advances in γδ T cell-based related immunotherapies, including cell engaging strategies and adoptive cell therapy.